If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2s + -6) + -12 = -2(7s + 8) + -2 Reorder the terms: -2(-6 + 2s) + -12 = -2(7s + 8) + -2 (-6 * -2 + 2s * -2) + -12 = -2(7s + 8) + -2 (12 + -4s) + -12 = -2(7s + 8) + -2 Reorder the terms: 12 + -12 + -4s = -2(7s + 8) + -2 Combine like terms: 12 + -12 = 0 0 + -4s = -2(7s + 8) + -2 -4s = -2(7s + 8) + -2 Reorder the terms: -4s = -2(8 + 7s) + -2 -4s = (8 * -2 + 7s * -2) + -2 -4s = (-16 + -14s) + -2 Reorder the terms: -4s = -16 + -2 + -14s Combine like terms: -16 + -2 = -18 -4s = -18 + -14s Solving -4s = -18 + -14s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '14s' to each side of the equation. -4s + 14s = -18 + -14s + 14s Combine like terms: -4s + 14s = 10s 10s = -18 + -14s + 14s Combine like terms: -14s + 14s = 0 10s = -18 + 0 10s = -18 Divide each side by '10'. s = -1.8 Simplifying s = -1.8
| 4y-6=y-6 | | 6y-9=2y+6 | | 8-4n=17-n | | 0.26(10000)-0.02y=0.08(y+10000) | | h=x-6x | | 0.75x+0.05(10-x)=0.10(47) | | 4y-7=-14-3y | | 0.12(6)+0.03x=0.06(12+x) | | (2x+3y-1)dx+(2x+3y+2)dy=0 | | (8x^2-5x+16)+(6x^2+9x-77)= | | (y-2)dx-(x-y-1)dy=0 | | 8n-(-2)=18 | | x^2+1+6=42 | | 8x-4=6+2 | | x^2+6x+9=15 | | -6t+2=3r | | -16t^2+0t^2=0 | | 7x+15=3(x+2) | | f(x)=5x-4 | | 5-2(3-x)=9(x-4) | | 7x-6x+2x-5x= | | 4-x=2(x+7)/3 | | f(x)=6x+6 | | 4(x+6)-17= | | 3(5x+4)/2+7x-8 | | 9y-14y+3= | | e^3x-1=0 | | 2(4x-5)/3=x+10 | | 4(2x-3)/5=4 | | 11w-14w=18 | | 2(5x+1)+5(x-2)= | | 8-4(-12x+3)= |